Adoption of electronic commerce by the small and medium enterprises for business-to-business dealings. - Chua, Khoon Hui. (2008)
This study examines the willingness of the small and medium enterprises (SMEs) in Singapore to adopt electronic commerce for business-to-business dealings. Viewing such a medium as a form of new innovation, the Rogers model of innovation decision process is applied as the framework. Summary statistics are analysed to find out factors that differentiate companies into those who are willing to adopt and those who are not willing to adopt electronic commerce.